Diversity, abundance, and distribution patterns of stingless bees (Hymenoptera: Meliponini) in Yogyakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Trianto M, Purwanto H. 2021. Diversity, abundance, and distribution patterns of stingless bees (Hymenoptera: Meliponini) in Yogyakarta, Indonesia. Biodiversitas 23: 695-702. Stingless bees (Hymenoptera: Meliponini) are eusocial insects with high economic value in terms of their honey and propolis yield. The bees are widely distributed in tropical regions, including Indonesia. This study aimed to estimate the diversity, abundance, and distribution pattern of stingless bees in the Special Region of Yogyakarta Province, Indonesia. The following seven species of stingless bees have been identified in previous research: Tetragonula laeviceps, T. iridipennis, T. biroi, T. sapiens, T. sarawakensis, Heterotrigona itama, and Lepidotrigona terminata. The current work determined the scores of diversity (H’: 0.98), abundance (N: 14.0 ind/m2), and distribution pattern (id: 0.51) of stingless bees in Yogyakarta, Indonesia. The results were analyzed and then subjected to principal component analysis to determine the dominant characteristics on the basis of the environmental parameters that influence the presence of stingless bees in three habitat types in the Special Region of Yogyakarta Province, Indonesia. Results revealed that temperature is one such environmental parameter affecting the presence of stingless bees in the Special Region of Yogyakarta, Indonesia.
Keywords: Abundance, distribution pattern, diversity, Stingless Bees, Yogyakarta